2018
DOI: 10.1007/s10802-017-0394-2
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping and Distinct Cognitive Impairments in Attention-Deficit/Hyperactivity and Autism Spectrum Disorder without Intellectual Disability

Abstract: Attention-deficit/hyperactivity disorder (ADHD) and autism spectrum disorder (ASD) are commonly comorbid, share genetic liability, and often exhibit overlapping cognitive impairments. Clarification of shared and distinct cognitive effects while considering comorbid symptoms across disorders has been lacking. In the current study, children ages 7-15 years assigned to three diagnostic groups:ADHD (n = 509), ASD (n = 97), and controls (n = 301) completed measures spanning the cognitive domains of attention/arousa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
91
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(107 citation statements)
references
References 62 publications
12
91
2
2
Order By: Relevance
“…Taken together, the lack of correlations across groups except for cue‐ and stimulus‐evoked PD amplitudes within ASD‐ may additionally indicate an increased effort to optimize task performance in children with ASD‐ (Rondeel, van Steenbergen, Holland, & van Knippenberg, ). Nevertheless, to further examine how the LC‐NE system modulates attention and task performance future studies should examine other, and more sensitive measures of (disorder‐specific) response execution in addition to RT (Karalunas et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the lack of correlations across groups except for cue‐ and stimulus‐evoked PD amplitudes within ASD‐ may additionally indicate an increased effort to optimize task performance in children with ASD‐ (Rondeel, van Steenbergen, Holland, & van Knippenberg, ). Nevertheless, to further examine how the LC‐NE system modulates attention and task performance future studies should examine other, and more sensitive measures of (disorder‐specific) response execution in addition to RT (Karalunas et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although our findings of greater delay discounting in ASD are contrary to some studies, existing literature is mixed. Some researchers have found evidence for greater discounting of future rewards in ASD (e.g., Carlisi et al, ; Chantiluke et al, ; Murphy et al, ), but others have found no group differences (e.g., Antrop et al, ; Demurie et al, ; Karalunas et al, & Kouklari, Tsermentseli, & Monks, in press). One possible explanation is that most studies finding differences, including ours, examined adolescents and adults, whereas most studies showing no differences included children as young as 7 or 8.…”
Section: Discussionmentioning
confidence: 99%
“…8 These disorders appear to share some genetic factors 9 and biological pathways, 10 although divergences in their neuro-biological, cognitive, and genetic profiles are apparent. 1113 Although some findings may be accounted for by the co-occurrence of ADHD and ASD 13 and others by heterogeneity within the 2 conditions, 14 it remains unclear how related these disorders are etiologically. It is important to further characterize the degree of shared etiologic risk across these impairing, prevalent, and complex conditions.…”
mentioning
confidence: 99%